Ceramide-CD300f binding suppresses experimental colitis by inhibiting ATP-mediated mast cell activation. Issue 5 (11th February 2015) - Matsukawa, Toshihiro; Izawa, Kumi; Isobe, Masamichi; Takahashi, Mariko; Maehara, Akie; Yamanishi, Yoshinori; Kaitani, Ayako; Okumura, Ko; Teshima, Takanori; Kitamura, Toshio; Kitaura, Jiro
Abstract : Objective: Extracellular ATP mediates mast cell-dependent intestinal inflammation via P2X7 purinoceptors. We have previously shown that CD300f (also called the leucocyte mono-immunoglobulin-like receptor 3 (LMIR3)) suppresses immunoglobulin E-dependent and mast cell-dependent allergic responses by binding to ceramide. The aim of the present study was to clarify the role of ceramide–LMIR3 interaction in the development of IBD. Design: The dextran sodium sulfate (DSS)-induced colitis model was used in wild-type (WT), LMIR3 −/−, mast cell-deficient Kit W-sh/W-sh, Kit W-sh/W-sh LMIR3 −/− or Kit W-sh/W-sh mice engrafted with WT or LMIR3 −/− bone marrow-derived mast cells (BMMCs). The severity of colitis was determined by clinical and histological criteria. Lamina propria cell populations were assessed by flow cytometry. Production of chemical mediators from lamina propria cells was measured by real-time reverse transcription PCR. Production of chemical mediators from ATP-stimulated BMMCs in the presence or absence of ceramide was measured by ELISA. The severity of DSS-induced colitis was assessed in mice given either an Fc fusion protein containing an extracellular domain of LMIR3, and anticeramide antibody, or ceramide liposomes. Results: LMIR3 deficiency exacerbated DSS-induced colitis in mice. Kit W-sh/W-sh mice harbouring LMIR3 −/− mast cells exhibited more severe colitis than those harbouring WT mast cells. Ceramide–LMIR3 interaction inhibited ATP-stimulated activation of BMMCs. DSS-induced colitis was aggravated by disrupting the ceramide–LMIR3 interaction, whereas it was suppressed by treating with ceramide liposomes. Conclusions: LMIR3-deficient colonic mast cells were pivotal in the exacerbation of DSS-induced colitis in LMIR3 −/− mice. Ceramide liposomes attenuated DSS-induced colitis by inhibiting ATP-mediated activation of colonic mast cells through ceraimide–LMIR3 binding.